Financial Investigation and Forensic Accounting to Averting of Corporate Fraud - Bansal, Atul (2017)
Financial investigation and Forensic Accounting have been in focus in recent years mainly due to an excess of frauds that have taken place in the corporate sectors.The value of frauds executed in these sectors has been very large and caused severe financial strain on individuals, corporations and the government.Many of these financial frauds could have been detected earlier and possibly avoided by the use of forensic accounting techniques.The aim of this study is to determine the financial investigation and Forensic Accounting to averting the frauds and misrepresentations in the corporate houses. The study attempts to identify the cause of frauds, the psychology of the typical fraudster, the warning signs of an impending or recurring fraud and measures to detect and prevent frauds.An analysis is made of Forensic Tools that can analyze data and detect unusual events that could act as an indicator of frauds.The study seeks to establish the forensic practices in vogue in the industry and its usage among the various professional categories of accounting professionals.The prospects of the profession, the educational and training requirements are also evaluated. The study also uses a high level forensic tool in a case study into the major Indian Cement companies to detect whether prima facie there has been a likely manipulation of the books of account.